Sunnah Sebelum Tadwin: Analisis Historis atas Pemikiran ‘Ajjaj Al-Khatib - Nana Gustiana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine Ajjaj al-Khatib’s views on the existence and authority of the Sunnah prior to the codification of Hadith, as articulated in his work al-Sunnah Qabla al-Tadwīn. The research adopts a qualitative method using content analysis of primary texts, supplemented by a literature review of related scholarly works. The findings reveal that al-Khatib affirms the presence and normative authority of the Sunnah within the Muslim community from the Prophet’s time until the pre-codification era. This continuity was maintained through oral transmission, the systematic education of the Prophet’s companions, and collective communal practice. The study concludes that al-Khatib presents an alternative narrative of Hadith transmission history through a critical-historical approach, offering a significant response to doubts concerning the authenticity of the Sunnah before its formal codification.